2004
DOI: 10.1177/104438940408500406
|View full text |Cite
|
Sign up to set email alerts
|

Components of an Aboriginal-Based Family Violence Intervention Program

Abstract: The purpose of the study was to describe the essential elements of an Aboriginal-based family violence intervention program. Twenty-one Aboriginal family violence program administrators and service providers were asked "What program components are essential in an Aboriginal family violence prevention program?" Respondents identified the need for sound administrative structure and function, qualified and healthy staff, and consistent program funding. Coordinated service delivery with other community agencies wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Cunneen (2001a) identified three themes as central to successful Indigenous rehabilitation and crime prevention programs: (a) enhancing self-determination, (b) holistic approaches, and (c) promoting empowerment rather than dependency. Others posit that successful Indigenous rehabilitative programs require local-level development in consultation with Indigenous communities (Cripps & Davis, 2013; facilitation by Indigenous staff and/or Elders (Brown & Languedoc, 2004); culturally specific content; an individual “healing” focus addressing spiritual and cultural loss (Boersig, 2007; McKendrick et al, 2017; Office of the Status of Women [OSW], 2001); engagement of the family, reconnection with homelands and traditional culture, and relevance to the life experiences of Indigenous people (Indigenous Justice Forum, Attorney-General’s Department, 2012; Royal Commission into Aboriginal Deaths in Custody, 1991; Trevethan et al, 2005; Willis & Moore, 2008). These contentions held by many Australian academics, Indigenous peoples, and their representatives (Brown & Languedoc, 2004; Cripps & Davis, 2012; OSW, 2001) are yet to be empirically tested.…”
Section: Factors Associated With Family Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Cunneen (2001a) identified three themes as central to successful Indigenous rehabilitation and crime prevention programs: (a) enhancing self-determination, (b) holistic approaches, and (c) promoting empowerment rather than dependency. Others posit that successful Indigenous rehabilitative programs require local-level development in consultation with Indigenous communities (Cripps & Davis, 2013; facilitation by Indigenous staff and/or Elders (Brown & Languedoc, 2004); culturally specific content; an individual “healing” focus addressing spiritual and cultural loss (Boersig, 2007; McKendrick et al, 2017; Office of the Status of Women [OSW], 2001); engagement of the family, reconnection with homelands and traditional culture, and relevance to the life experiences of Indigenous people (Indigenous Justice Forum, Attorney-General’s Department, 2012; Royal Commission into Aboriginal Deaths in Custody, 1991; Trevethan et al, 2005; Willis & Moore, 2008). These contentions held by many Australian academics, Indigenous peoples, and their representatives (Brown & Languedoc, 2004; Cripps & Davis, 2012; OSW, 2001) are yet to be empirically tested.…”
Section: Factors Associated With Family Violencementioning
confidence: 99%
“…Subsequent to these findings, the NSW Department of Justice requested development of a culture-specific DV rehabilitation program suitable for Indigenous men. The applicability of the DAP to the needs of Indigenous men was questioned, as the program was neither facilitated by local Indigenous Elders, nor included any culture-specific content as recommended by Cripps and Davis (2012 & 2013) and Brown and Languedoc (2004).…”
Section: First Evaluation Of the Domestic Abuse Programmentioning
confidence: 99%
“…In studying these issues, case studies and/or interviews are often the methods of choice. Brown and Languedoc (2004) investigated essential program components of an Aboriginal family violence program in Canada. The authors conclude that program components should be based on traditional teachings, should create awareness of personal and family dynamics and change, and should educate about family violence.…”
Section: 2mentioning
confidence: 99%
“…These responses are based on Western models of intervention that separate the needs of victims and perpetrators (Cripps & McGlade, 2008). Furthermore, research has found that family violence programmes working with indigenous groups need to see a person, their family, and their community as interconnected (Brown & Languedoc, 2004). Many Western approaches to family violence fail to do this.…”
Section: Ethnicitymentioning
confidence: 99%
“…Many Western approaches to family violence fail to do this. Western systems take either an individual approach, seeing the violence as caused by the perpetrators psychopathology; a familial approach, seeing the family system as being out of balance; or a social system approach, linking violence to males having greater power than females (Brown & Languedoc, 2004). Each of these approaches fails to take into account the complex interconnections between individuals, families, and their communities.…”
Section: Ethnicitymentioning
confidence: 99%